Ocean Circulation Model Applications for the Estuary-Coastal-Open Sea Continuum - Murawski, Jens; She, Jun; Mohn, Christian; Frishfelds, Vilnis; Nielsen, Jacob Woge (Frontiers in Marine Science, 2021)
Coastal zones are among the most variable environments and require adaptive water management to ensure that economic and social interests are balanced with environmental concerns. Prediction of hydrographic conditions e.g., sea level, temperature, salinity and currents in coastal-estuary continuum is the basis for climate change adaptation and mitigation and ecosystem-based management in coastal waters. Operational model and service capacities are needed, that cover the coastal-estuary scale in hundreds of meter or higher resolution and that bridge the gap to the local and basin scale models in kilometer resolution. Limfjord, a fjord connecting Kattegat and North Sea, is currently not covered by CMEMS service, despite its importance for sea shipping, aquaculture and mussel fisheries. In this study, we use the two-way nested operational HIROMB-BOOS Model (HBM) to resolve the Baltic-Limfjord-North Sea system with the Limfjord domain in about 185m horizontal resolution. The results show several essential factors for successfully modelling the coastal-estuary system: high computational efficiency and flexible grids to allow high resolution in the fjord, a special thermodynamics to resolve vertical air-sea-soil heat exchange for very shallow waters and accurate river forcing and bathymetry in narrow straits. With properly resolving these issues, this system is able to provide high quality sea level forecast for storm surge warning, temperature, salinity and currents with reasonably good quality for ecosystem-based management. The model is able to handle the shallow thermoclines in summer as well as the strong tidal and wind driven transport through narrow straits in autumn and winter. Its high computational efficiency makes it possible to model the transition from the basin-scales to coastal- and estuary-scales seamlessly.